Associations between the red blood cell distribution width-to-albumin ratio and 3-month outcomes in patients with acute minor ischemic stroke: A cohort study - Qin Chen; Qin Xiong; Li Liu; Lei Xu (PLoS ONE, 2025)
Acute minor ischemic stroke (AMIS) patients may experience unfavorable outcomes despite mild initial symptoms. The ratio of red blood cell distribution width (RDW) to albumin (ALB) (RAR) has been associated with poor outcomes after stroke, but its role in AMIS remains unclear. This study aimed to investigate the association between the RAR and 3-month functional prognosis in patients with AMIS. This is a secondary analysis of a single-center, prospective cohort study conducted in Korea that included 988 patients with AMIS with a National Institutes of Health Stroke Scale (NIHSS) score ≤3. The RAR was calculated using RDW and ALB levels measured within 24 hours of admission. The functional outcome at 3 months poststroke was assessed using the modified Rankin Scale (mRS). The associations between the RAR and poor 3-month outcomes (mRS score ≥3) were evaluated using a multivariable logistic regression model, adjusting for confounders and conducting stratified and sensitivity analyses. Multivariate regression analysis revealed that the RAR was significantly associated with poor prognosis, both when it was unadjusted (OR = 2.29, 95% CI: 1.74–3.02, P < 0.0001) and after adjusting for age and sex (OR = 2.18, 95% CI: 1.63–2.91, P < 0.0001) and for multiple confounders (OR = 2.44, 95% CI: 1.67–3.57, P < 0.0001). Subgroup analysis revealed that the association between the RAR and poor prognosis was consistent across all subgroups. Elevated RAR is significantly associated with poor 3-month functional outcomes in patients with AMIS.